Number of seeds in fruits and frequency of hybrids obtained in crossings with IAC 2019Maria mandarin - Roverssi, Fernanda; Cavichioli, Thais Magni [UNESP]; Curtolo, Maiara; Latado, Rodrigo Rocha; Yaly, Mariângela Cristofani (FapUNIFESP (SciELO), 2022)
The Citrus Breeding Program of the Citriculture Center at the Agronomic Institute (IAC) has developed a mandarin cultivar IAC 2019Maria from the crossing between Murcott IAC tangor (Citrus reticulata x Citrus sinensis) and Pera IAC sweet orange (C. sinensis). The present study aimed to assess the number of seeds in fruits of IAC 2019Maria mandarin and to identify zygotic embryos and triploid plants in the crossings between IAC 2019Maria mandarin, Pera IAC sweet orange, and Ponkan mandarin (C. reticulata Blanco), in addition to IAC 2019Maria mandarin in open and self-pollination. IAC 2019Maria flowers were self-pollinated, pollinated with pollen from Pera sweet orange and Ponkan mandarin, and had no pollination. The embryos were identified using microsatellite molecular markers and ploidy was assessed by flow cytometry. The results of the treatment with no pollination suggest the variety does not produce parthenocarpic fruits. The genotyping results showed that 100% of the populations consist of zygotic embryos, suggesting that IAC 2019Maria mandarin is a plant with low polyembryony. The ploidy analysis of the hybrids allowed identifying a triploid plant from an aborted seed from the crossing with Pera sweet orange and two tetraploids, one from the crossing with Pera sweet orange and one from self-pollination.
Número de sementes em frutos e frequência de híbridos obtidos de cruzamentos com a tangerina IAC 2019Maria
Keywords: genetic improvement; IAC 2019Maria; triploidy; Zygotic embryo